Pattern of Rheumatic Heart Disease in Western Nepal - an Echocardiographic study: a single centre experience - KC, Bishal; Gautam, Samir; Dhungel, Sachi; Hirachan, Anish; Khan, Mazhar; Shakya, Abhishesh; Panjiyaar, Rajesh (Journal of Advances in Internal Medicine, 2023)
BACKGROUND AND AIMS Rheumatic heart disease (RHD) is a preventable but chronic debilitating sequela to the acute rheumatic fever. It takes several years for manifestations, however can present early in places with high prevalence. Most common valve involved are mitral and aortic. Echocardiography is simple tool to diagnose the presence as well as quantify the valvular lesion. This study aims at identifying the pattern of valvular involvement in RHD in community heart center in western Nepal. METHODS This was a retrospective analysis of the patients presenting with Rheumatic heart disease over the period of two years from July 2020 to July 2022. RESULTS Altogether 563 echocardiograms with diagnosis of RHD were recorded over the period of two years. The mean age was 33.59±12 years. The commonest age group involved was 21-40years (56.66%). Overall, there was female preponderance over male, 77.4% vs 22.6%. Isolated MR was the commonest among the isolated lesion (64.44%). Multivalvular lesion was more common than isolated lesions 76.03% vs 23.97%. Isolated mitral stenosis (MS) and isolated mitral regurgitation (MR) was more common in female 82.1% and 758% respectively whereas isolated aortic regurgitation (AR) was more common in male (55%). Involvement was in the order of MS+MR>AR+MR>MS+AR>AS+AR>MS+AS>AS+MR in the cases of multivalvular lesion. Mean mitral valve area was .2±0.39 cm2. Among the MS, 65(19.69%) had mild, 145(43.93%) had moderate and 120(36.36%) had severe lesion and all were common in female and the age group 21-40years. Mild, moderate and severe MR was more common in female while severe AR was found only in male. Overall, 271(48.13%) had pulmonary hypertension and was more common in severe MS. CONCLUSION Valvular heart disease is common and the most common lesion is RHD in developing country like ours. This study shows that RHD is more common in female and middle age group. Multivalvular lesion is more common than the isolated lesions.